Pengaruh Inovasi Produk dan Harga Terhadap Keputusan Pembelian Sepeda Motor Honda di Kota Bekasi - Utama, Dani Chandra (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
This study aimed to analyze the impact of innovation and price on purchase decisions. The research was carried out at different places to get a full range of respondents. The sample was the owner of the vehicle Honda motorcycle in Bekasi totaling 150 respondents. Regression analysis techniques were used to analyze the impact of innovation and price of the purchasing decision is by using SPSS (Statistical Package for the Social Sciences). The analysis showed that the product innovation and significant positive effect on purchasing decisions, each increase of one unit in the variable product innovation will be followed by an increase of 0.401 unit purchasing decisions. The analysis also showed that prices positive and significant influence on purchasing decisions, any adjustment of the unit either affordability of the price, the suitability of the price of the product quality, price competitiveness, and suitability prices with benefits will influence the purchase decision of Honda motorcycles for 0538 unit. This shows that the innovation products made by Honda  and Prices set affects 46.6% of the consumer decision in purchasing undergo a Honda motorcycle in Bekasi.